Usefulness of Reid Colposcopic Index (RCI) in the analysis of colposcopic images - Kłosiński, Witold; Jędrzejczyk, Sławomir; Guzowski, Grzegorz; Klimek, Hanna; Sieroszewski, Piotr (Menopause Review/Przegląd Menopauzalny, 2012)
Objectives : The aim of the study was to estimate the usefulness of Reid Colposcopic Index (RCI) in the analysis of colposcopic changes observed in uterine cervix during colposcopy examination. Moreover, we estimated a correlation between the RCI scale and histopathology outcomes. Material and methods : In our study we included 145 patients hospitalized between October 2009 and July 2010 in H. Jordan’s Hospital in Lodz at the Operative Gynecology Ward. Cytologic smears and colposcopic examinations with colposcopy-directed biopsy were performed in all of the patients. All the images which were saved during colposcopy were evaluated using the RCI index. Results : We observed a strong correlation between histopathology outcomes of biopsied tissues and RCI outcomes from the colposcopy examination. Additionally, we confirmed the connection between the grade of the dysplastic process of uterine cervix in cytology and colposcopy and RCI summary outcome. Conclusion : Usage of RCI makes it easier to classify colposcopic images and increases a correlation between colposcopic and histopathology outcomes.